An open chat with…Beáta Vertessy. Issue 2 (11th February 2021) - Tsagakis, Ioannis; Vertessy, Beáta; Wright, Duncan
Abstract : As FEBS Open Bio approaches its 10th anniversary, we have decided it is an ideal time to give the members of our prestigious Editorial Board an opportunity to discuss their research, publishing, and the activities of FEBS in the virtual pages of the journal. This new interview series is being helmed by Professor Beata Vertessy, who has been on the FEBS Open Bio Editorial Board since 2013 and has recently been promoted to Senior Editor. As the organizer, she has agreed to give the inaugural interview.